Assistance In Financial Management of Karampuang Island Tourism Towards International Tourism - Bulutoding, Lince; Rahmah Sari, Nur; Ambo Masse, Rahman; Hasbiullah, Hasbiullah; Suhartono, Suhartono; Jannah, Raodahtul; Sumarlin, Sumarlin; Elfa Syariati, Namla; Marsanda, Marsanda; Reski Ananda Putri, Andi; Reza Pahlevi, Ashraf; Adam Nursya Ban, Muh.; Musdalifa, Musdalifa (CV. Inara, 2024)
This study aims to analyze and assist in the financial management of tourism on Karampuang Island with the hope of increasing the island's tourist appeal for foreign visitors. The methods used in this study are literature study and Focus Group Discussion (FGD). Through literature study, data and information regarding best practices of financial management in the tourism sector were taken from various literature, journals and related documents. Furthermore, FGD was conducted by involving local stakeholders, including tourism attraction managers, local communities, and government officials. This activity aims to explore ideas, challenges, and solutions related to sustainable tourism financial management. The results of the FGD show that many tourism actors on Karampuang Island still experience difficulties in managing finances effectively. Therefore, training and assistance in budget management, financial recording, and marketing planning are needed. It is hoped that with this assistance, tourism actors can improve their managerial capacity and develop effective strategies to attract foreign tourists. These findings form the basis for formulating policy recommendations that support the development of sustainable tourism on Karampuang Island.